Regional localization on the human X of DNA segments cloned from flow sorted chromosomes. - Kunkel, L M (1982)
Fluorescence activated sorting of chromosomes from 49,XXXXY human lymphoblasts has been used to obtain DNA enriched for the human X. This DNA was cloned in lambda phage Charon 21A to obtain a library of approximately 60,000 pfu. Phage inserts free of human highly repeated DNA sequences are localized to different regions of the human X by two independent hybridization analyses. The first utilized comparative hybridization to rodent-human hybrid cell DNA samples containing all or known portions of the human X, while the second was based on hybridization dosage to DNA samples from human cell lines differing in the number of X chromosomes or X chromosome segments. Of five unique sequence inserts tested, three were X chromosome specific and were localized to regions Xpter leads to Xcen, Xql leads to Xq22 and Xq24 leads to Xqter, respectively. The library presented here represents a highly enriched source of human X chromosome-specific DNA sequences.